Implementasi Kebijakan Pendidikan Karakter Di Madrasah Tsanawiyah Muhammadiyah Al Manar Kabupaten Demak - Prasetyo, Arif Rahman (Tribakti: Jurnal Pemikiran Keislaman, 2020)
This study describes the implementation of character education policy in MTs Muhammadiyah Al Manar Demak Regency. This type of research is descriptive qualitative. Data collection techniques using observation, interview, and documentation. Data validity test uses triangulation of data sources. The results of research are; (1) Programs that support character education are Islamic learning integration, flag ceremonies, extracurricular activities, philanthropic box, recording of mutaba'ah sheets, lecture after dawn and maghrib, studying at night, living in boarding school, muhadharah and muwada'ah, Ramadan activities, and commemoration of Islamic holidays. (2) The implementation of character education policies is supported by systematic communication, committed human resources, sufficient funding sources, maximum time allocation and clear bureaucratic structure lines.